Restaurant Business Development Strategy (Study On Sambalado Restaurant Jl. Pancing No.25 Medan) - Irfal Khairin Hamdi (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2020)
Typical of Minang restaurant is one business that many entrepreneurs they work with the consideration that the Minang cuisine preferably all walks of society. It sparked intense competition among minang restaurant . Yet when viewed from the types of products offered, typical eating house minang have very little differentiation and even tend to be similar. Thus, a typical mnang restaurant business requires the right strategy in order to continue to survive and thrive. Therefore, Restaurant Sambalado has to arrange appropriate business development strategy to be home eating can compete competitively.The purpose of this study was to assess and determine the destination business development strategy on Restaurant Sambalado at Pancing Road No. 25 Medan based on the results of SWOT analysis, analysis of IFAS and EFAS and External Internal analysis.Forms of research used in this research is descriptive using qualitative data analysis. Methods of data collection is done by observation, interview and documentation study. Data were analyzed using IFAS and EFAS matrix, the matrix SFAS, SWOT matrix and the matrix IE.The results showed that the current Restaurant Sambalado have the strength and a great opportunity to be competitive. Based on the analysis that the strategy should be applied to Restaurant Sambalado must support the policy of aggressive growth (growth-oriented strategy). This strategy is designed to achieve growth, both in sales, assets, profits, or a combination of all three. This can be achieved by lowering the price, developing new products, increasing the quality of products or services, or by improving access to the market which is more extensive, the intensive strategy. Besides.